Pedagogical prospects in academic spaces based on melodrama and Brazilian circus-theater (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This paper presents part of a doctoral research whose investigation focus is the creation process of the theatre play "Por Ti Não Importa Matar ou Morrer", a free adaptation of the work "Vem Buscar-me Que Ainda Sou Teu", by the author Carlos Alberto Soffredini, from the performance codes of French melodrama and the elements of circus arts, performed in the Theater Course at the Federal University of Uberlândia in 2015. For the analysis of this process, acting references of Brazilian circus-theater were used, considering the trajectory of Circo-Teatro Guaraciaba. This article contextualizes the ways in which the theater became part of circuses in Brazil in order to support the understanding of artistic and pedagogical experiences and to establish a dialogue between the history of 19th century French melodrama and the 20th century Brazilian circus-theater, evidenced through reflections about the learning ways of the old guard circus performers and young actresses and actors from universities.
Keywords: Circus-theater; Medlorama; Theater pedagogy; Creative processes